0656 Validation of the Self-administered Version of the International Restless Legs Syndrome Study Group Severity Rating Scale - the sIRLS. (12th April 2019) - Sharon, Denise; Allen, Richard P; Martinez-Martin, Pablo; Walters, Arthur S; Ferini-Strambi, Luigi; Högl, Birgit; Trotti, Lynn-Marie; Buchfuhrer, Mark J; Swieca, John; Bogan, Richard K; Zak, Rochelle; Becker, Philip M
Abstract: Introduction: The International Restless Legs Study Group (IRLSSG) has developed the IRLS (International Restless Legs Syndrome Severity Scale) and validated it as a clinician/researcher administered scale to be used when both patient and examiner are present. The IRLSSG recognized the need for a self-completing scale that can be used economically in clinical practice to assess patients and evaluate treatment outcomes as well as in large population-based studies. In this study the validity and the reliability of the IRLS as a self-administered scale (sIRLS) is assessed. Methods: Established RLS patients were recruited by eight centers in four countries and consented to participate in this study. The validity of the sIRLS was assessed by patients completing the sIRLS before a clinician administered the IRLS. The reliability of the sIRLS was assessed by patients completing the sIRLS again, two weeks after the first one, provided no change had occurred. Results: 173 patients were recruited and 164 of them were included in the analyses. The sIRLS showed satisfactory scaling assumptions and no relevant floor or ceiling effect. One factor explained 61.3% of the variance. Cronbach's alpha was 0.93 and the item homogeneity index was 0.59. Intraclass correlation coefficient between the sIRLS and the IRLS was 0.94. The sIRLS standard error of measurement was 3.61 (½ SD at baseline=4.11). The results mostly overlapped those of the IRLS analyzed in parallel. Conclusion: The sIRLS is a reliable, valid and precise instrument that showed tight association with the IRLS. These findings support the use of the sIRLS for self-evaluation of RLS severity. The sIRLS validity and reliability support its use in evaluating the quality of care of RLS patients. The responses obtained on the sIRLS and the IRLS scales varied slightly. Therefore, we recommend that either the sIRLS or the IRLS scale be used as the only scale for serial measures over time. Support (If Any): Limited financial support for this study was provided by the International Restless Legs Syndrome Study Group (IRLSSG).